Power Transformer Condition Assessment Using Oil UV - Spectrophotometry - Arshad, M; Islam, Syed (IEEE Dielectrics and Electrical Insulation Society, 2007)
Power transformers are considered critical equipment in an electric power transmission system. Electric utilities worldwide are now focusing on reliability centered maintenance of their assets for extended life and hence maximum return on investment. Recent utility survey shows that a large proportion of transformers has attained their designed life and is operating close to their nameplate rating or beyond. The load growth is compounding this problem on the existing transformers due to fewer extension projects, market deregulation and economic constraints. Diagnostics and proper monitoring plays key role in the life expectancy of a power transformer. Mineral oil in transformer is the inseparable component of the dielectric insulation system. The various contamination levels in oil can be examined and verified using UV-Spectrometry. The UV-spectrum analyzes the oil, qualitatively and quantitatively with respect to the contamination present in it and interprets dielectric response of the insulation system. The oil gets contaminated mainly due to the aging. Moisture, sludge, acids, metal particles and other compounds are produced due to aging insulation (mainly cellulose) which changes the oil chemical and physical properties. Accurate interpretation of the UV-Spectrophotometry and comparison with the past test signature provides sufficient assessment of power transformer insulation condition and predicts it's aging phenomena. This paper presents power transformer's dielectric response and aging assessment using oil contamination level identification with UV-Spectrometry measurements.